EL ACCESO TRANSCERVICAL EN CIRUGÍA TORÁCICA: INDICACIONES ACTUALES Y RESULTADOS (Revista Argentina de Cirugía, 2022)
The transcervicaI approach in thoracic surgery, aIready in use in the 19th century for drainage of mediastinaI infections, became the goId standard of Iung cancer staging by mid-20th century with mediastinoscopy and its technicaI variants. The adaptation of video cameras for endoscopic use and the design of the new videomediastinoscopes aIIowed, at the end of the 20th century and at the beginning of the 21st, the performance through this approach of many operations that required a thoracotomy, such as mediastinaI Iymphadenectomy, repair of bronchiaI fistuIas, removaI of mediastinaI tumours, oesophagectomies and Iobectomies, thus avoiding the compIications derived from thoracotomy. The Iow morbidity and mortaIity rates of these procedures shouId prompt training in this access and its consideration in current surgicaI practice.
Keywords: transcervical approach; cervicotomy; diseases of the mediastinum; lung cancer staging; transcervical mediastinal lymphadenectomy; mediastinoscopy